Rebuilding worker power in Australia through multi-employer bargaining. (3rd July 2021) - Kennedy, Tim; Redford, Ben; Burns, Renee; Forsyth, Anthony
ABSTRACT: The Australian Council of Trade Union's Change the Rules campaign from 2017 to 2019 demanded enterprise bargaining be redesigned to fit the modern world of work. Unions argued collective bargaining should not be limited to the outdated framework of the 'enterprise'. Workers should be able to bargain with the host business in labour hire; with franchisors; with lead businesses in supply chains; and across industries. In this article, we undertake a preliminary analysis of the key issues for consideration in designing multi-employer bargaining in the Australian context. We review the United Workers Union's experience in whole-of-supply-chain bargaining through its Fresh Food Campaign, and draw upon recent proposals for multi-employer bargaining from the UK Institute of Employment Rights, and the Harvard 'Clean Slate' Project in the USA. We examine the shape of worker bargaining units for purposes of multi-employer bargaining; employee support thresholds; the permitted scope of bargaining; and the legal effect of multi-employer agreements. While its precise shape requires much further consideration, the case for implementing this change in Australian labour law is even stronger in the wake of the COVID-19 pandemic: not only to boost workers' economic power, but to ensure they have control over the safety of their work.